PREVENTION OF POSTOPERATIVE LIVER FAILURE IN HIGH-RISK PATIENTS WITH ACUTE DESTRUCTIVE CHOLECYSTITIS (Global Conference on Medical and Health Sciences, 2026)
Elderly patients with acute destructive cholecystitis and severe comorbidity often have limited hepatic reserves, and radical surgery in this group carries a high risk of postoperative liver failure, which aggravates the postoperative course and increases mortality. A dedicated method for preventing postoperative liver failure in high-risk patients has not been sufficiently developed.